Avaliação dos mecanismos de ação do peptídeo sintético Mo-CBP3-PEPIII contra Candida spp. através de bioquímica quântica e simulações de dinâmica molecular. - Amaral, Jackson Lima (2019)
Candida is the principal group of opportunistic pathogens in humans and is responsible for 8 to 10% of the bloodstream infections at Intensive Treatment Unit. There has been observed a great increase in the microorganism resistance to current strategies, raising a necessity to develop new drugs with a greater spectrum of action. The antimicrobial peptides are indicated as the most promising drug alternative with a better cost-effective, a broad spectrum of action and a low resistance induction. Based in a purified protein from Moringa oleifera with high microbial activity, Mo-CBP3, our research group designed a synthetic antimicrobial peptide, named Mo-CBP3-PEPIII, with antimicrobial activity 130-fold higher compared to Mo-CBP3. In this work, we demonstrated the possible mechanism of actions of this synthetic peptide through in silico approaches with keys enzymes: sterol 14-α demethylase, secreted aspartic proteases, β-1,3-glucanase and with realistic membrane of yeast. First, we analyzed the interactions using molecular docking, followed by a simulation of molecular dynamics for 20 ns with the enzymes and 150 ns with the yeast membrane. Finally, we calculated the interaction energies between Mo-CBP3-PEPIII and the key enzymes applying quantum biochemistry. Although Mo- CBP3-PEPIII presented no interaction with the catalytic site of sterol 1,4-alpha demethylase, it showed interaction with secreted aspartic protease 5 and β-1,3- glucanase in active site, presenting interaction energy of -104.9 kcal/mol and -122.2 kcal/mol, respectively. In the simulation of molecular dynamics was possible to observe the insertion of the Mo-CBP3-PEPIII into the yeast membrane. Altogether, the results indicate that the mechanism of action differs from azoles drugs and the interaction with other key enzymes can be an alternative mechanism of action. Thus, it can be inferred that the mechanism of action crucial is the penetration of the Mo- CBP3-PEPIII into the membrane and pore formation. Mo-CBP3-PEPIII has a great potential to be a new drug with a broad spectrum of action